Effect of targeted therapy and immunotherapy on advanced nonsmall‐cell lung cancer outcomes in the real world. (16th November 2021) - Shokoohi, Aria; Al‐Hashami, Zamzam; Moore, Sara; Pender, Alexandra; Wong, Selina K.; Wang, Ying; Leung, Bonnie; Wu, Jonn; Ho, Cheryl
Abstract: The evolution of diagnosis and treatment of advanced nonsmall‐cell lung cancer (NSCLC) has led to increasing the use of targeted therapy and immune checkpoint inhibitors. The study goal was to assess the effect of molecular testing and the introduction of new therapies on overall survival (OS). All patients with stage IV NSCLC referred to BC Cancer were included in the study. Four 1‐year time cohorts were created based on molecular testing implementation and funded drug availability: C1 baseline (2009), C2 EGFR TKI access (2011), C3 ALK inhibitor access (2015), C4 immunotherapy availability (2017). Baseline demographics, disease characteristics, and systemic therapy details were collected retrospectively. OS was calculated using the Kaplan–Meier method and compared using the log‐rank test. There were 3421 patients identified with stage IV NSCLC and 1319 (39%) received systemic therapy. In the four 1‐year time cohorts C1/C2/C3/C4: driver mutation‐targeted treatment increased 1/17/27/34% (of total systemic therapy), as did treatment with any line immunotherapy <1/1/9/38%. Median OS with best supportive care (BSC) was 3.4/3.1/3.2/2.9 m ( p = 0.16) and with systemic treatment 9.9/10.9/13.9/15.0 m ( p < 0.001). Median OS by treatment exposure was BSC 3.1 m, chemotherapy only 7.3 m, targeted therapy 17.5 m, and immunotherapy 20.7 m. In our real‐world study, following the introduction of targeted therapy and immune checkpoint inhibitors, there was a significant improvement in OS in each successive time cohort concordant with advancements in therapeutic options. Abstract : We evaluated outcomes with new therapies in 3421 patients with advanced nonsmall‐cell lung cancer. There was an improvement in survival over time with the introduction of EGFR, ALK, and immunotherapy. The median OS by treatment strategy was BSC 3.1 months, chemotherapy alone 9.2 months, driver mutation receiving targeted therapy 17.5 months, and immunotherapy in any line 20.2 months. Our findings in a real world demonstrate that it is critical to identify patients appropriately for emerging systemic therapies.